Hazardous Waste Management in Turkey - Akkoyunlu, Atilla; Avsar, Yasar; Erguven, Gokhan Onder (ASCE-AMER SOC CIVIL ENGINEERS, 2017)
The objective of this study is to analyze the time processes of hazardous waste management (HWM) in Turkey. There should be a holistic evaluation of a country's hazardous waste management program in terms of theoretical qualifications, best practice applications, and, of course, problems and their solutions. This paper offers a similar approach to evaluate HWM in compliance with the European Union under the laws of environmental applications. In 2010, 786,418 tons of hazardous waste (HW) were produced in Turkey. Of this, around 18% is sent to municipal garbage dumps, 0.6% is burned, and the remaining 81.4% is disposed of by other methods (such as controlled landfill or haphazard throwaways). (C) 2017 American Society of Civil Engineers.
Keywords: Hazardous waste; European Union (EU) directives; Management; Legal chronology; Inventory; Engineering